OPTIMIZATION MODEL OF LAND USE PLANNING TO REDUCE LAND EROSION LEVEL: CASE STUDY IN THE UPPER CIUJUNG RIVER BASIN - Soentoro, Edy Anto; Muhardiono, Imam; Suryadi, Yadi (Institut Teknologi Bandung, 2019)
AbstractUncontrolled changes in land use located in the upstream river can result in land erosion, which will eventually increase river sedimentation as well as floods, reduce the estimated planned life of the downstream reservoir, and reduce soil productivity due to the loss of nutrients. This study is aimed to find the best land use pattern through optimization, in order to reduce the level of land erosion. The optimization model used is the Linear Programming (LP) method which is combined with the USLE method and Geographic Information System software based on raster grids. The potential sedimentation prediction that is collected from the measurement data in the river is used to calibrate the simulation of the real conditions of land erosion. The optimization results of this study in the Upper Ciujung river basin, Banten, can be obtained by expanding as much as possible the area of corn-fields/moors to become plantations (which are denser and bigger tree fields) or even forests. The results can reduce the level of land erosion by 38.0%, or from 99.03 tons/ha/year to 61.32 tons/ha/year. However, the results above cannot be generally applied in all locations. What can be generally accepted is that the optimization model of this study can be used to reduce the level of land erosion by regulating the size of the area and location of each type of land use, and by considering the factors of soil erodibility, slope, and rain erosivity at the site.AbstrakPerubahan tata guna lahan yang tidak terkendali di daerah hulu aliran sungai dapat mengakibatkan erosi lahan, yang pada akhirnya akan meningkatkan sedimentasi di sungai dan banjir, mengurangi umur rencana waduk di hilirnya, serta menurunkan produktivitas tanah karena lapisan hara yang hilang. Penelitian ini ditujukan untuk mencari pola tata guna lahan yang terbaik dengan cara optimasi guna mengurangi tingkat erosi lahan. Model optimasi yang digunakan adalah metode program linier (LP) yang digabung dengan metode USLE dan software SIG (system informasi geografis) berbasis raster grid. Prediksi potensi sedimentasi dari data pengukuran sedimen di sungai digunakan untuk kalibrasi simulasi kondisi nyata erosi lahan. Hasil optimasi pada penelitian di Sub DAS Ciujung Hulu, Provinsi Banten, bisa didapat dengan merubah seluas mungkin areal ladang/tegalan yang sudah ada untuk menjadi kebun campuran atau hutan. Hasilnya dapat memperkecil tingkat erosi lahan sebesar 38,0%, atau turun dari semula sebesar 99.03 ton/ha/thn menjadi 61,32 ton/ha/thn. Namun hasil tersebut diatas tidak bisa berlaku secara umum di semua lokasi. Yang bisa berlaku umum adalah bahwa model optimasi dari studi ini dapat dipakai untuk mengurangi tingkat erosi lahan dengan mengatur luas areal dan penempatan lokasi jenis-jenis penggunaan lahan, dengan mempertimbangkan faktor erodibilitas tanah, kemiringan lereng, dan erosivitas hujan di lokasi.